Constructing Our Environments: A Material Comparison - Murdock, Henry (University of Waterloo, 2014)
Our built environment is constantly adapting to changing factors: technology, the state of the economy, material resource availability, and, in turn, environmental conditions. The latter has gained notable importance in popular discourse, and especially in the architecture and construction professions. However, as much as we see terms such as “sustainability” and “green” in our everyday lives, government and industry are slow to take action investing in our future environment. Material resources in the building industry are worth investigating. Timber, used as a structural material to compete with concrete and steel, brings more energy efficient and natural renewable resources to our growing cities. In order to provide a broader perspective of how we as a society use concrete, steel, and timber, I will compare the three building materials in a four part guideline: Environmental Performance, Ease of Manufacture, Organized Assembly, and Design Flexibility. Each section provides insight into how we shape these three materials. I argue, based on the rating evaluation, for the benefits, using cross-laminated timber in cities like Toronto.
Keywords: Sustainability; timber; Cross-laminated timber; building economics; material manufacturing; Architecture